CUDA-Based Particle Swarm Optimization in Reflectarray Antenna Synthesis - Capozzoli, A.; Curcio, C.; Liseno, A. (Advanced Electromagnetics, 2020)
We show how reflectarray antenna synthesis can take profit from parallel computing on Graphics Processing Units (GPUs). The presented approach uses an implementation of Particle Swarm Optimization in CUDA language and accelerates the computation of the field radiated by the reflectarray using a GPU- mplemented Non-Uniform FFT routine. Numerical results show how computing time can be kept convenient for the application at hand.